2012
DOI: 10.1007/s10530-012-0172-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphological differentiation in a common garden experiment among native and non-native specimens of the invasive weed yellow starthistle (Centaurea solstitialis)

Abstract: Understanding the differences between weedy and non-weedy plant populations is important because they may provide clues to genetic factors that create invasive species, as well as important insights into local adaptation. We studied weedy, non-native (California and Argentina) and non-weedy, native populations (Republic of Georgia and Turkey) of Centaurea solstitialis in a common garden setting. Specimens grown from non-native seed stock were generally taller, had longer leaves with more surface area, and flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…2C,D). Higher reproductive output of larger invaders supports a previous inference of adaptive size evolution in this invasion, based on size differences exceeding expectations from molecular differentiation (Q ST > F ST ) 25 .…”
supporting
confidence: 80%
“…2C,D). Higher reproductive output of larger invaders supports a previous inference of adaptive size evolution in this invasion, based on size differences exceeding expectations from molecular differentiation (Q ST > F ST ) 25 .…”
supporting
confidence: 80%
“…Invading populations are persistent and difficult to control (Aslan et al, ; Matzek & Hill, ). Genotypes from invaded regions have evolved larger seeds, larger biomass, faster growth rates, shorter time to flowering, and greater reproductive output than those from the Eurasian native range (Dlugosch, Cang, et al, ; Eriksen, Desronvil, Hierro, & Kesseli, ; Widmer, Guermache, Dolgovskaia, & Reznik, ). Invading populations in the Americas achieve densities that are more than an order of magnitude higher than those in the native range (Andonian et al, ; Uygur, Smith, Uygur, Cristofaro, & Balciunas, ).…”
Section: Methodsmentioning
confidence: 99%
“…Several invading populations show evidence of additional recent admixture with other native populations (Barker et al, ; Dlugosch, Lai, Bonin, Hierro, & Rieseberg, ; Eriksen et al, ). Phenotypic studies have revealed evolutionary increases in plant size during this range expansion, which is associated with higher fitness (Dlugosch, Cang, et al, ; Eriksen, Desronvil, Hierro, & Kesseli, ; Widmer, Guermache, Dolgovskaia, & Reznik, ). Experimental crosses in C. solstitialis provide an opportunity to better understand how admixture might be influencing the success of invading lineages.…”
Section: Methodsmentioning
confidence: 99%
“…Progeny ( N = 523, including 1–3 per cross) were reared for growth measurements in the common glasshouse environment. Increased growth is a fundamental metric of heterosis in experimental crosses (Birchler et al, ; Chen, ), and it is a key trait whose evolution is associated with increased fitness in invasions of C. solstitialis (Dlugosch, Cang, et al, ; Eriksen et al, ). All size measurements of both “source” genotypes (produced by within‐population crosses) and “admixed” genotypes (produced by among population crosses) were made in the same experiment, at both 4 and 5 weeks of age (Supporting Information Figure ).…”
Section: Methodsmentioning
confidence: 99%